Description of Difficulty of Semester VII Students of Mathematics Education Study Program in Complex Analysis Course - Jitu Halomoan Lumbantoruan (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2022)
The purpose of this research is to find out how the students' mastery and difficulty lies in direct objects and indirect objects in complex variables courses. Two mathematical indicators are direct object and indirect object. The direct object is related to understanding Facts (definitions), Concepts (ideas, thought patterns), Skills (general and specific skills), and Principles (Formulas, theorems and postulates). While indirect objects are media and tools. In 2014/2015 students in the Complex Variables course received UTS, there were 13% good scores and 77% less good. Another fact is that in 2019/2020, 30 students took complex variables, there were 50% less good and 15 others were of sufficient value, good and very good. Of the 50% who were not good, took remedial and only 10 people graduated, the remaining 5 people did not pass and had to repeat the next semester. The research method used is descriptive qualitative. Techniques to get data from observation, interviews and documentation. The analysis technique is to present, reduce and draw conclusions. The results of the analysis, observation, interviews and documentation intersect and show the location of the dominant difficulty in the direct object, 100% of sources think that the mastery of facts is weak (Definitions), 85.71% of concepts and skills, and 57.14% of principles. Difficulty connecting old material with new material is due to weak mastery of facts. In observation, a new problem arises when writing symbols on the media used. The ability of students to write symbols for complex variables makes the atmosphere of the discussion group percentage process unstructured. In conclusion, 100% believe that they do not master the facts, and this becomes another difficulty in mastering complex variables. New findings, in complex variable courses cannot use the online learning process.